Meaning Analysis of ???? and ???? Emojis in Chat Apps: A Semiotic-Semantic Study - Yumeina, Fariha Faza; Nabila, Hana; Dewi, Lusiana Suciati (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2024)
This research discusses the meaning of ???? and ???? emojis in chat apps. The ???? emoji is often used to express sadness or frustration, while the ???? emoji is often used for dark humor or to express that something is so funny it's "dead". This study aims to explore and reveal the meanings contained in these emojis according to the general views of chat app users. This research uses a qualitative approach with a focus on the description and interpretation of the phenomenon of emoji use. The main data source comes from direct observation of conversations in chat applications, as well as secondary data from related literature. Data collection techniques include participatory observation of emoji use in different contexts and analysis of conversation documentation. The results of this study are expected to provide a deeper understanding of how ???? and ???? emojis are used and interpreted in daily interactions, as well as how their meaning can change depending on the context of the conversation.